KEPUTUSAN DETERMINAN PERUSAHAAN DALAM REVALUASI ASET TETAP (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI) - Ratih Dewi Titisari Haryana; Annisah Febriana (Fakultas Ekonomi dan Bisnis Universitas Wijaya Putra, 2023)
Fixed asset revaluation is an action that can be requested back accurately to describe the true value of a company's assets. Based on PSAK 16 companies in Indonesia can choose the cost method or the revaluation method on their fixed assets. The purpose of this study is to determine the factors that influence the revaluation of fixed assets in manufacturing companies listed on the Indonesia Stock Exchange (IDX). It is predicted that the factors influencing the revaluation of fixed assets are leverage, firm size and fixed asset intensity. The statistical method used in this research is descriptive statistics and logistic regression. The sample used in this study were manufacturing companies in the basic and chemical industry sectors in 2019-2021 which were listed on the IDX. The sampling technique used purposive sampling technique. The results of this study indicate that the leverage factor has a significant effect on the revaluation of fixed assets. Meanwhile, the firm size factor and the proportion of fixed assets have no significant effect on the revaluation of fixed assets.